JURNAL PENGARUH KEPRIBADIAN PROAKTIF DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DPRD KOTA TERNATE - RINI SABAN; Marwan Man Soleman; Ruslan A. Kamis (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Abstract Rini Saban, Department of Human Resource Management (MSDM) Faculty of Economics and Business Khairun University "UNKHAIR" Ternate. The title of the research is "The Influence of Proactive Personality and Work Motivation on the Performance of Ternate City DPRD Secretariat Employees". Under the guidance of Marwan Man Soleman and Ruslan A Kamis. The purpose of this study was to determine the effect of proactive personality and work motivation partially on employee performance at the DPRD Secretariat of Ternate City. The analytical model used to test the hypothesis is multiple linear regression analysis, and the research method used is explanatory research with a quantitative approach and a sample of 46 respondents. With data processing techniques using SPSS 16 for windows. The results of this study prove that: (1) Proactive personality has a positive and significant influence on employee performance, which means that the better the employee's proactive personality, the better the employee's performance. (2) Work motivation has a positive and significant effect on employee performance, which means that work motivation that can be felt by employees at work will be able to improve employee performance. Simultaneously, proactive personality and work motivation have a positive and significant effect on employee performance. Keywords : Proactive Personality, Work Motivation and Employee Performance